Deep Brain Stimulation of Caudal Zona Incerta and Subthalamic Nucleus in Patients with Parkinson's Disease: Effects on Voice Intensity. (19th October 2011) - Lundgren, Sofie; Saeys, Thomas; Karlsson, Fredrik; Olofsson, Katarina; Blomstedt, Patric; Linder, Jan; Nordh, Erik; Zafar, Hamayun; van Doorn, Jan
Abstract : Deep brain stimulation of the subthalamic nucleus (STN-DBS) in patients with Parkinson's disease (PD) affects speech inconsistently. Recently, stimulation of the caudal zona incerta (cZi-DBS) has shown superior motor outcomes for PD patients, but effects on speech have not been systematically investigated. The aim of this study was to compare the effects of cZi-DBS and STN-DBS on voice intensity in PD patients. Mean intensity during reading and intensity decay during rapid syllable repetition were measured for STN-DBS and cZi-DBS patients (eight patients per group), before- and 12 months after-surgery on- and off-stimulation. For mean intensity, there were small significant differences on- versus off-stimulation in each group: 74.2 (2.0) dB contra 72.1 (2.2) dB (P = .002 ) for STN-DBS, and 71.6 (4.1) dB contra 72.8 (3.4) dB (P = .03 ) for cZi-DBS, with significant interaction (P < .001 ). Intensity decay showed no significant changes. The subtle differences found for mean intensity suggest that STN-DBS and cZi-DBS may influence voice intensity differently.